The characterization of management processes in higher education institutions in Mozambique. Collegiality, managerialism and other conjugated factors - Omar, M. N.; Pereira, R. (JANUS.NET, e-journal of International Relations, 2020)
This article discusses the transposition of the principles normally applied in business management to Higher Education Institutions (HEI). In particular, it discusses the influence exerted by managerialism in the structuring and operation of Higher Education Institutions. In the empirical study conducted in Mozambique, the positions of different actors on different dimensions and categories of the problem are analyzed, supported by a methodology of qualitative analysis from a sample of 9 IES. The main conclusions reveal that in Mozambican higher education there remains a certain resistance from the higher education communities, particularly from its professionals, to the intrusion of managerialism, highlighting a position favorable to collegiality and democracy. Despite the existing criticism, some (minority) actors recognize the influence of managerialist contributions to the objectives of higher education and the design and materialization of HEI management, proposing a hybrid model that associates the two dimensions. The study also reveals a deficit in the participation of the higher education community in management and decision-making processes, making it difficult to apply the collegial model.